Memoria e inteligencia: interdependencia en función de los procesos y contenidos de las tareas - Ferreira, A.; Almeida, L.; Prieto, G.; Guisande, M. A. (Universitas Psychologica, 2012)
is study investigates the characteristics of the specific memory factors (processes and content) that are associated to the Gsm from the CHC model. Memory tasks with different content, including various aptitude tests and a general intelligence test, were administered to a sample of university students. Two models that relate the general Gsm aptitude, with working memory and memory span, and with verbal-numerical and visual-spatial aptitudes were tested. Results indicate good fit indices for both models tested, as well as evidence for a positive regression between Gsm and working memory and between Gsm and visuospatial content. In both models we observed standardized regression of 0.54 and of 0.73 between Gsm and factor g. Implications for the understanding of the relation between memory and intelligence are discussed.